Perancangan Desain Karakter Buku Ilustrasi People pleaser Dalam Dunia Kerja - Eulogize Gracia Putri Manullang; Restu Ismoyo Aji; Aris Sutejo (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
This paper discusses the visual design of character designs for an illustrated book that focuses on the problem of people pleasers among employees aged 22-30 years. People pleasers are individuals who tend to please others at the expense of themselves, which in the long term can trigger stress and mental disorders. The results of the study show that many young employees experience a dilemma between meeting other people's expectations and maintaining their own well-being. To convey this problem, four characters were designed. The main character is Tara, a people pleaser who undergoes a transformation into a more balanced individual in her work and personal life. Three supporting characters help strengthen the dynamics of conflict in the workplace, Mr. Johnson (Tara's demanding boss), Shinta (a supportive co-worker), and Felix (a senior co-worker). The character design process was carried out through several stages, including interviews with psychologists, illustrators, and employees, as well as qualitative data analysis from observations, Focus Group Discussions (FGD), and literature studies. The result is four characters executed in a simple illustration style with flat design and a limited color palette to emphasize the emotional atmosphere experienced by the characters. By exploring the right illustration style and color composition, this study designs characters that not only depict the reality of people pleasers in the workplace, but also function as visual educational media that helps readers understand the importance of setting boundaries at work and supports individuals in achieving inner peace and balance in life. Keywords: People pleaser, Persona, Illustration, Employee Character Design